Hubungan Faktor Predisposing Kader (Pengetahuan dan Sikap Kader terhadap Posyandu) dengan Praktik Kader dalam Pelaksanaan Posyandu di Wilayah Kerja Puskesmas Wonokerto - Rr. Vita Nur Latif (Pena Medika Jurnal Kesehatan, 2011)
Background & Methode : Related  Knowledge and attitude of cadre with the Cadres Practice in Posyandu in Job distric of “Puskesmas Wonokerto” Pekalongan Regency; based on The number of Mother Mortality Rate (MMR) in Pekalongan district had 161/100.000 birth live, one of  the aim “Posyandu” was to decrees MMR by the cadres practicing “posyandu”. The aim of this study was to analizy and identify the related knowledge and attitude of cadre with the cadres practice in posyandu in job distric of “Puskesmas Wonokerto” Pekalongan Regency.This study was an explanatory research using cross sectional approach, using 70 partisipant. Result : The result was showed Knowledge had related with cadres practice    ( p value 0.003) and attitude had related with cadres practice (p value 0.006).Keywords : Knowledge, attitude of cadre, Cadres Practice in Posyandu